(untitled) (Proceedings of the International Conference on Future of Education, 2021)
The creation of virtual environments and their implementation have been a matter of greatest importance in the last decades, becoming a breaking point for progress in different fields like communication, entertainment, and education. Additionally, the learning and teaching of human biology have been more relevant through the increase of biology-related research and medical advances. However, learning human biology, especially anatomy, is perceived as difficult by students. The objective of this study is to improve the learning of human biology by implementing a Virtual Reality Program (VRP) in a high school human biology course, measuring academic performance in a final knowledge evaluation. The VRP used immersive Virtual Reality (VR) devices (Oculus-Go® and Oculus-Rift®) and consisted of three stages: exploration, virtual reality lab, and knowledge reinforcement. In the exploration, the students had a guided approach of the topics with a professor’s explanation; afterward, they had guided and independent collaborative experience in the Virtual Reality lab; and finally, their knowledge was reinforced in communication with the professor. A post-test only with a control group design was employed with 120 students. There were two experimental groups (63 students) and two control groups (57 students). After completing the stages of the VRP, all the groups had a final knowledge evaluation where the experimental groups obtained a mean of 77.24, while the control groups had 69.11. There was a significant statistical difference between the groups with a P<0.05 using a two-sample t-test. This proves that implementing a long-time and collaborative immersive VR approach in high school human biology courses is effective for enhancing learning and improving academic performance.